Pencegahan ISPA Berbasis Masyarakat Melalui Edukasi dan Skrining Kesehatan di Desa Manduro Kabupaten Mojokerto - Aliyah Sundari; Dwi Wahyu Indriati; Nur Septia Handayani (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2026)
This community service activity aims to improve residents’ knowledge and awareness of acute respiratory infections (ARI), while strengthening the role of local health cadres through education and health screening. A total of 30 participants took part in the program, which included initial coordination, a baseline understanding survey, educational sessions and interactive discussions, distribution of educational materials, as well as blood pressure and hemoglobin examinations. Program evaluation was conducted using questionnaires analyzed descriptively. The results showed that all participants experienced systolic hypertension, some had diastolic hypertension, and the majority were identified with polycythemia. House-cleaning behavior and adequate rest were categorized as very good (100%), while the use of masks during air pollution exposure reached 81.5%. However, exposure to cigarette smoke inside the home remained high (48.1%), and poor indoor air humidity conditions were frequently reported. Post-education knowledge scores increased significantly, indicating that presentation methods and interactive discussions were effective in improving participants’ understanding of ARI and its prevention measures. Therefore, the ARI education program in Manduro Village made a positive contribution to improving community knowledge and preventive behavior and should be continued sustainably in high-risk areas.